2017
DOI: 10.1590/s2175-97902017000300204
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and cytotoxic activity of Tecoma stans against lung cancer cell line (A549)

Abstract: Human have been constantly using plants and plant products to overcome many diseases. The antioxidant property of the plant sources is studied to obtain an efficacious drug against cancer. The objectives of the present study is to evaluate the antioxidant and cytotoxic activity of the Tecoma stans extracts against lung cancer cell line in comparison with vincristine drug. The antioxidant activity was studied using the standard DPPH assay and the cytotoxic activity using MTT assay. DPPH assay results show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…However, it also suggests that this effect is dependent on the kind of solvent used to extract the compounds. In many studies, caspase activity has been shown to be more commonly activated in methanolic extracts [16][17][18][19] . Many in vitro and in vivo studies have shown many medicinal plants as promising for the treatment of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it also suggests that this effect is dependent on the kind of solvent used to extract the compounds. In many studies, caspase activity has been shown to be more commonly activated in methanolic extracts [16][17][18][19] . Many in vitro and in vivo studies have shown many medicinal plants as promising for the treatment of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Methanolic extract of Careya arborea at the concentration of 10 ug/ml and 20 ug/ml exhibited the decreased cell viability, however with a concentration at 40ug/ml showed a non-significant difference. This is possibly due to the fact that, we used a crude methanolic extract of the plant, which contains numerous useful and unusual bioactive compounds [16]. Distilled water extract of the plant showed increased cell viability, suggesting its non-potential to treat A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tecoma stans was tested against A549 (human lung adenocarcinoma) cell line and cell viability was reduced in a dose-dependent manner, indicating a moderate cytotoxic effect [49]. Another study showed that the plant extract was cytotoxic against HepG2 cells where a reduction in viability of cancer cells was observed [50].…”
Section: Bignoniaceaementioning
confidence: 99%